Recinto de exposición comercial y empresarial” Barrio Restrepo: plan de renovación comercial Restrepo (2016)
Commerce and business exhibition venue: this project contributes to the Restrepo industry needs related to reorganize commercial activities due to the international market points to the competition because their low prices relegate the market of Restrepo industry pushing it away and relegating to a second level the quality that characterizes market. That's why the project emerges as an international commercialization window where tech workforce will excel and the quality of supplies will be recognized so the economy reflected in a long- term and setting aside the Chinese offer as a principal competitor since they offer economy but never quality al all.